Overview of the Scientific, Political and Financial Landscape of Climate-Smart Agriculture in West Africa - Zougmoré, Robert B.; Traoré, Alain S.; Mbodj, Yamar (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
The agricultural sector plays a key role in the Economic Community of West African States (ECOWAS). As the backbone of the economy, it affects society at many levels since national economies and people’s jobs, incomes and food security depend upon it. Climate change and variability pose a major threat to farmers in the region, which is already experiencing rising temperatures, shifting precipitation patterns, and increasing extreme events. The ECOWAS has put in place various policy instruments such as the Economic Community of West Africa States Agricultural Policy (ECOWAP) and its derived Regional Agricultural Investment Plan (RAIP) in order to promote a modern and sustainable agriculture based on effective and efficient family farms and the promotion of agricultural enterprises through the involvement of the private sector. Taking stock on member States’ expressed needs, ECOWAS would like to integrate a new type of public policy instruments into the RAIP: instruments for adapting the West-African agriculture to climate change, towards a Climate-Smart Agriculture (CSA) focusing on adaptation, mitigation and food & nutrition security joint objectives. This book documents and analyses specific features of the scientific, institutional, policy and funding CSA landscape in West Africa. It provides relevant information that could guide the definition of the ECOWAS Framework for CSA Intervention, Funding, Monitoring and Evaluation. Five major agricultural sectors have been covered: crop production, livestock, fisheries, forestry/agroforestry, and water. For each sector, a particular emphasis was given to the current status, the climate projections and likely socio- economic and environmental impacts expected, the bottlenecks to action and suggested next steps for adaptation and mitigation. Actionable messages and recommendations have been directed to ECOWAS stakeholders so as to incentivise CSA in West Africa. Key words: Climate change ; Climate-smart agriculture ; Crop production ; Livestock ; Water resources ; Fisheries ; Forestry ; Agroforestry ; West Africa